“O TRAUMA E A FERIDA NA MEMÓRIA”: Literatura latino-americana e narrativas sobre os regimes ditatoriais no Brasil e Chile - MELO, Rafael Passos de (2022)
This study aims to reflect about how the Literature has sometimes included historical facts on its plots, as dictatorships and repressions imposed by military regimes. For this reason, this work’s goal is to establish an analysis of representations checking the power relations’ role on the narrative constitution as well as speeches in specific situations. From it, it was studied how these narratives might have a role on the emersion of complex contexts establishing, even if ficcionally, possible statements from the scene portrayed. Amid this study debates, it has been emphasized the relevance of a historical consciousness related to those events promoting reflections about how testimony literature can contribute to this knowledge upon the continuous challenges founded by the History and Sociology researchers. To reinforce this study, it is brought the historical moment in which the Latin America countries, Brazil and Chile, were divided ideologically in the face an alleged threat from a communist spectrum which demanded political organization efforts from both sides, even if they were favorable to the military regimes or the ones classified as clandestines lives. Therefore, the theoretical notes by Seligmann-Silva (2008), Dellamore (2011) and Ginzburg (2002) were fundamental to the construction of the highlighted arguments.